Coming out of invisibility: new challenges for soil science - Etchevers-Barra, Jorge D.; Cotler-Ávalos, Helena; Hidalgo-Moreno, Claudia (REVISTA TERRA LATINOAMERICANA, 2020)
The ecosystem functions and services that soils provide are essential for quality human life and are immersed, though not explicitly, in seven of the Sustainable Development Goals (SDGs). However, in Mexico, soil deterioration is increasing, to the extent that it is a threat to food security. Despite extensive soil research by the country’s various public institutions, the results of this research do not permeate in public policies. In the face of this absence, new forms of research arise, where interdisciplinary and transdisciplinary dialogues are necessary, and new approaches to study must be attended individually and as part of the Mexican Society of Soil Sciences.